Process intensification using mixed sequential and integrated hybrid cryogenic distillation network for purification of high CO2 natural gas - Maqsood, K. (Institution of Chemical Engineers, 2017)
A framework for mixed sequential and integrated hybridization (MSIH) based intensification is proposed for cryogenic CO2 capture from natural gas. Formulation and evaluation of the intensified cryogenic distillation network is also investigated. The present work attempts to experimentally quantify the liquid and solid formation during cryogenic CO2 capture and the separation efficiencies obtainable in real life under cryogenic temperature and high pressures in presence of their complex dynamics and interactions. Synthesis, sensitivity analysis and evaluation were performed for side mounted switched cryogenic desublimation beds integrated with the distillation column in the cryogenic network. The advantages of mixed integrated hybrid cryogenic distillation network over base case and sequential multibed hybrid networks are highlighted and presented. Optimization of each network has been carried out using the real life efficiencies and experimental solid and liquid formation data. Optimization of mixed sequential and integrated cryogenic network showed promising potential through reduction in energy consumption, hydrocarbon losses and footprints. © 2016 Institution of Chemical Engineers